On the risk spillover from Bitcoin to Altcoins: The fear of missing out and pump-and-dump scheme effects - Mehmet Balcilar; Huseyin Ozdemir (Journal of Risk and Financial Management, 2023)
This article examines the asymmetric volatility spillover effects between Bitcoin and alternative coin markets at the disaggregate level. We apply a frequency connectedness approach to the daily data of 11 major cryptocurrencies for the period from 1 September 2017 to 2 March 2022. We try to uncover the existence of the "fear of missing out" psychological effect and "pump-and-dump schemes" in the crypto markets. To do that, we estimate the volatility spillovers from Bitcoin to altcoin and the cryptos' own risk spillovers during bull and bear markets. The spillover results from Bitcoin to altcoin provide mixed results regarding the presence of this theory for major cryptocurrencies. However, the empirical findings carried out by the cryptos' own spillover effects fully confirm the existence of a fear-of-missing-out effect and pump-and-dump schemes in all cryptocurrencies except for USDT.
Keywords: C32; E42; E49; G14; G41; 650; cryptocurrency; bitcoin; altcoin; asymmetric volatility spillover; frequency connectedness